THE APPROACH OF IBN TABATIBA AL-ASBAHANI TO THE ISSUE OF WORD AND MEANING CASTING AND THE PROBLEMATIC ARTISTIC IMAGERY - Ad-dakhil, Mohammad Majid (Laboratorium Informasi & Publikasi Fakultas Humaniora UIN Maulana Malik Ibrahim Malang, 2014)
This study shows that intends to address the issue of